A formação profissional e a aplicação dos modelos de periodização do treinamento desportivo, por treinadores de judô de atletas de elite - Tavares Junior, Antonio Carlos [UNESP] (2014)
Judo emerged in Japan in 1882, becoming an Olympic sport in 1964, and it is one of the most practiced sports in the world nowadays.Its introduction into Brazil has occurred in early twentieth century, as a result of Japanese immigration. Thus, historically, the training of judo coaches in Brazil has been developed through an empirical model, characterized by the master/disciple relation. However, both the current requirements and the high complexity of modern sports have strongly driven the sports preparation into a scientific background, being that the sports coach has been the central figure of this process, responsible for leading, coordinating and structuring these demands to achieve the desired goals. Among the conceptions of sports science, it should be highlighted those regarding to structuring and periodization models of training, once these assumptions are the basis for planning, preparation, and control of the variables which compose the sports training field. Thus, the aim of this study was to investigate the planning and preparation process of sports preparation applied by judo coaches of high level athletes, in a manner to understanding the influence of their training process to become a judo coach (empirical/artisanal and/or scientific/professional) in the selection process or preparation of the training model applied, by a multiple case study, having the periodization models of sports training as theoretical background. Data were collected through an interview composed of two parts, the first one about the profile of the interviewed, and the second one consisted in a semi-structured interview with questions regarding to the periodization model utilized. The sample was composed by young coaches (between 32-42 yrs.), with important results in tournaments, graduated in physical education, being that 6 of them had postgraduation educational level. The results showed that all participants have utilized scientific principles in...